2008
DOI: 10.3382/ps.2007-00329
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-γ Gene: A Key Regulator of Adipocyte Differentiation in Chickens

Abstract: The peroxisome proliferator-activated receptors (PPAR) are members of the nuclear hormone receptor superfamily. Peroxisome proliferator-activated receptor-gamma is regarded as a "master regulator" of adipocyte differentiation in mammals. The current study was designed to investigate the function and regulatory mechanism of PPARgamma in chicken adipogenesis by RNA interference. Preadipocytes were isolated from the abdominal fat tissue of 12-d-old chickens and cultured. Small-interference PPARgamma RNA (siPPARga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 28 publications
2
47
0
3
Order By: Relevance
“…[14][15][16][17] In the current study, we found that gKLF3 overexpression suppressed chicken C/EBPα promoter activity in DF1 cells and chicken preadipocytes (p < 0.01; Fig. 5).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[14][15][16][17] In the current study, we found that gKLF3 overexpression suppressed chicken C/EBPα promoter activity in DF1 cells and chicken preadipocytes (p < 0.01; Fig. 5).…”
Section: Discussionmentioning
confidence: 53%
“…Effects of gKLF3 overexpression on promoter activities of important genes in adipose tissue C/EBPα and PPARγ are two master positive regulators of adipogenesis in mammals and birds. [14][15][16][17] We investigated the effects of gKLF3 overexpression on the promoter activities of C/EBPα and PPARγ using luciferase reporter assay. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Starting on day 0, chicken FSH (Zhonghao Biological Technology Co., LTD, Beijing, China) was included in the media at concentrations of 0, 5, 10, or 20 mIU/ml. Every 2 days, cell morphology, proliferation ( 29 ), and lipid content ( 30 ) were determined in triplicate wells from each treatment. Total RNA was also prepared from three wells and stored for q-PCR and microarray analysis.…”
Section: Fshr Mrna and Its Protein Are Expressed In Adipose Tissue Ofmentioning
confidence: 99%
“…Further, the increased LDL concentration indicated that large amounts of fat are transported out of the liver through VLDL and hydrolyzed by LPL, as remnants of hydrolyzed VLDL are found in the LDL form (Hermier 1997). We also found increased expression of PPARγ, which is a key regulator of chicken preadipocyte differentiation (Wang et al 2008). The up-regulated mRNA level of PPARγ in capon adipose tissues implied that caponization enhanced adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 62%
“…In particular, PPARγ is a key regulator of chicken preadipocyte differentiation (Wang et al 2008); its expression increases with differentiation of adipocytes, and reaches a peak when adipocytes get mature (Fan et al 2011).…”
Section: Introductionmentioning
confidence: 99%